2021
DOI: 10.1038/s41598-021-89317-x
|View full text |Cite
|
Sign up to set email alerts
|

Voxel and surface based whole brain analysis shows reading skill associated grey matter abnormalities in dyslexia

Abstract: Developmental dyslexia (DD) is the most prevalent neurodevelopmental disorder with a substantial negative influence on the individual’s academic achievement and career. Research on its neuroanatomical origins has continued for half a century, yielding, however, inconsistent results, lowered total brain volume being the most consistent finding. We set out to evaluate the grey matter (GM) volume and cortical abnormalities in adult dyslexic individuals, employing a combination of whole-brain voxel- and surface-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…In contrast, McGrath and Stoodley (2019) found increased gray matter volume in the SG for individuals with dyslexia compared to controls. Such controversies with respect to lateralized findings appear to be consistent with previous work (i.e., Kujala et al, 2021;Richlan, 2012;Yan et al, 2021) and support the notion put forward by Leonard and Eckert (2008) that underscored the importance of considering laterality. Given adults with dyslexia have either undergone treatment or have developed their own compensatory mechanisms, it will be essential to look at both hemispheres and the potential trade-offs that might contribute to their reading abilities.…”
Section: Supramarginal Gyrussupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, McGrath and Stoodley (2019) found increased gray matter volume in the SG for individuals with dyslexia compared to controls. Such controversies with respect to lateralized findings appear to be consistent with previous work (i.e., Kujala et al, 2021;Richlan, 2012;Yan et al, 2021) and support the notion put forward by Leonard and Eckert (2008) that underscored the importance of considering laterality. Given adults with dyslexia have either undergone treatment or have developed their own compensatory mechanisms, it will be essential to look at both hemispheres and the potential trade-offs that might contribute to their reading abilities.…”
Section: Supramarginal Gyrussupporting
confidence: 89%
“…When considering individuals with reading impairments, the IFG is just one notable region where functional and structural differences/abnormalities exist (D'Mello & Gabrieli, 2018; Eckert, 2004; Yan et al., 2021). The TPJ, which includes the STG and SG, has also been highly noted in dyslexia research (i.e., decreased gray matter for individuals with dyslexia) (Braid & Richlan, 2022; D'Mello & Gabrieli, 2018; Kujala et al., 2021; Linkersdörfer et al., 2012; McGrath & Stoodley, 2019; Soriano‐Ferrer & Piedra Martínez, 2017; Yan et al., 2021). Indeed, the IFG is structurally connected with the TPJ via the arcuate fasciculus (AF) (Verly et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a structural imaging study in dyslexic patients, voxel-based and surface-based analyses partly revealed coexistent gray matter findings, while in general, more morphological changes were revealed by voxel-based measures. 74 These findings support the notion that automated voxel-based calculations rely on different variables such as cortical volume and surface area. In addition, to avoid false positives, which were observed in a voxel-based study in which unequal group sizes led to inflated false positive rates, 75 we matched individuals that received placebos by and learning group (by content), sex and age.…”
Section: Discussionsupporting
confidence: 72%
“…24,25 In addition, the left superior temporal, left insula, as well as subcortical areas in DD also exhibited signs of reduced gray matter volume and cortical thickness overlapping, according to Kujala et al in 2021. 26 These alterations are associated with lower reading and phonological test scores. 27 Home literacy environment (parental education, socioeconomic status)…”
Section: Neurobiology Of Dyslexia Brain Anatomy and Dyslexiamentioning
confidence: 99%